2014
DOI: 10.1158/1940-6207.capr-13-0289
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Evolution of Somatic Chromosomal Alterations: A Case-Cohort Study of Barrett's Esophagus

Abstract: All cancers are believed to arise by dynamic, stochastic somatic genomic evolution with genome instability, generation of diversity and selection of genomic alterations that underlie multi-stage progression to cancer. Advanced esophageal adenocarcinomas (EAs) have high levels of somatic copy number alterations. Barrett’s esophagus (BE) is a risk factor for developing EA, and somatic chromosomal alterations (SCAs) are known to occur in BE. The vast majority (~95%) of individuals with BE do not progress to EA du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
217
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(239 citation statements)
references
References 68 publications
(109 reference statements)
22
217
0
Order By: Relevance
“…This observation is supported by the data in previous studies (Li, 2014; Gu et al, 2010). We showed that such correlation pertains to probes that are distant away (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is supported by the data in previous studies (Li, 2014; Gu et al, 2010). We showed that such correlation pertains to probes that are distant away (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…TP53 mutations, chromosomal instability, and genome duplication were observed in nearly all samples as early events. These fi ndings support the results from a previous longitudinal case-control study that showed increased chromosomal instability, genome duplication, and genome diversity in samples obtained from patients with Barrett's esophagus as they approached the diagnosis of esophageal adenocarcinoma ( 6 ).…”
supporting
confidence: 89%
“…In both cancer progressors and nonprogressors, large, stable clones have been found that consist of cells with loss of heterozygosity (LOH) for chromosomes 9p and 17p in BE (Buas et al 2014;Li et al 2014) and those with distinct CpG island methylation signatures in colorectal adenomas (Luo et al 2014.). As mentioned previously, a field effect caused by early common mutations in TP53 have also been found in BE segments , and similarly in patients with UC (Leedham et al 2009;Galandiuk et al 2012) and lung cancer patients (Franklin et al 1997;de Bruin et al 2014;Pipinikas et al 2014).…”
Section: Microenvironment Within Premalignant Diseasementioning
confidence: 66%